Challenges to Turning Nutrition & Agriculture Research into Action:A Case Study of NGO Research Uptake in Nepal. - Biehl,Erin.; Manohar, Swetha.; Gauchan, D.; Magar, M.; Pokhrel, P.; West, Keith.; Klemm, Rolf. (Tufts University. Tisch Library., 2017)
This study identified 1) the key factors influencing NGOs use of scientific evidence to inform the design and implementation of nutrition and/or agriculture programs in Nepal 2) common barriers to research uptake and 3) recommendations for overcoming these barriers. Understanding the challenges to turning nutrition and agriculture research into action will help ensure that scientific knowledge of nutrition and agriculture interventions is optimally used by implementing organizations in Nepal.